Inflexional Variants of the Type ‘Bagaży // Bagażów’ in the Contemporary Polish Language - Ruszkowski, Marek (Respectus Philologicus, 2018)
This article describes variants of the plural genitive of masculine nouns with variant endings – ów//-y (more seldom -i). Personal nouns are syncretic with accusative forms, i.e. czarodziei // czarodziejów; kuracjuszy // kuracjuszów; przybyszy // przybyszów. 40 pairs of variants of the type krokodyli // krokodylów were analysed. They were verified in terms of linguistic norm and frequency. The first verification was based on the determinations made in The Great Dictionary of Correct Polish Usage (GDCPU) published by PWN (in Polish: Wielki słownik poprawnej polszczyzny PWN), while the second one was based on The National Corpus of the Polish Language available in an electronic form.Out of 40 pairs of nouns, only 9 pairs have the ending -ów , which accounts for 22.5%. These are personal nouns (cywilów, czarodziejów, pedofilów, przybyszów, uczniów) and inanimate impersonal nouns (napojów, rodzajów, słojów, zwojów). Some of them are more frequent, as they are: 1. the only correct forms (pedofilów, zwojów); 2. non-colloquial, meaning they are recommended to be used in a carefully spoken and written Polish language (rodzajów, uczniów; colloquially rodzai, uczni); 3. non-jargonistic (cywilów; jargonistic – cywili); 4. regarded as seldom (przybyszy). Out of 8 pairs of forms treated by GDCPU as totally variant, only 3 pairs have the ending -ów (czarodziejów, napojów, słojów). The frequency of two first pairs is more than 90%, while the frequency of the form słoi is 77%. The share of napoi is only 3.6%, although it is also a form of a verb napoić (i.e. On napoi konie). It may seem that a scope of variants of the analysed forms is large. However, a considerable part of doublets are forms that are considered seldom, archaic, colloquial, jargonistic or inconsistent with the language norm. Thus, the thesis of a substantial variant occurrence of such types of forms should be verified.
Keywords: Genitive; Inflexional Variants; Frequency